Livros escolares de leitura: uma morfologia (1866-1956) - Antônio Augusto Batista Gomes; Ana Maria de Galvão Oliveira; Karina Klinke (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2002)
The present study makes use of the partial results of a research of broader scope. It aims to describe the morphology of the school reading book during the period 1866 1956. Schoolbooks constitute the major source of the investigation, particularly those that make up the collection of CEALE/ UFMG. These are taken to constitute an example of a school library, and therefore, an indirect representative of the production of books in Brazil during the period in question. The study reveals the existence of two major types of books (i.e. graded series and individual books), four major book genres (compendiums, anthologies, narratives and exercise books) and five major models of books (palaeographic, instructive, formative, rhetoricalliterary and autonomous). The study also allowed the identification of four phenomena, whose role in the make up of these classifications requires further investigation, namely, the progressive distinction between two types of reading in schools (reading in order to learn how to read and reading for pleasure); the relationship between the forms of the book and the progressive consolidation of the school and its agents; the relationship between reading books in Brazil and in France; the uses of books and their appropriateness for every-day educational activities.